Workflow for investigation of Out of Specification results in physico-chemical laboratory in Alkaloid - Andrea Alagjozovska; Milena Dobrkovikj Shotarovska; Maja Mindoseva; Stefan Petrovski; Gordana Mitrovska; Sanja Despotovska; Ornela Kuzmanovska; Elizabeta Karadzinska; Olivera Paneva (Makedonsko Farmacevtski Bilten)
The efficient and accurate investigation of Out of Specification (OOS) results is crucial in maintaining the reliability and quality of products in a physico-chemical laboratory. This paper presents a comprehensive workflow designed to systematically and effectively manage OOS results in such laboratories. The workflow integrates established quality assurance principles, regulatory guidelines, and best practices to ensure robust and reliable investigations. The presented workflow comprises several key stages, each designed to address specific aspects of the investigation process. The workflow provides a structured and systematic approach to investigating OOS results in physico-chemical laboratories. By incorporating data-driven decision-making, root cause analysis, and corrective actions implementation, laboratories can uphold product quality, regulatory compliance, and customer satisfaction. This workflow serves as a valuable tool for laboratories seeking to enhance their OOS investigation processes and overall quality management systems.